CUSTOMER SATISFACTION WITH GREEN BANKING INITIATIVES: INSIGHTS FROM SBI IN MAHABUBNAGAR (International Journal of Food and Nutritional Sciences, 2022)
Green banking represents a proactive initiative by financial institutions to promote environmentally friendly investments and sustainable practices. It is a concept that integrates environmental and social considerations into banking operations. Its primary goal is to safeguard the environment while fostering sustainable development. Unlike traditional banking, green banking prioritizes financing projects and industries committed to eco-friendly practices or transitioning towards sustainability. This approach not only supports environmental restoration but also encourages technological advancements and sustainable business models.